Prioritizing Infrastructure Investment : A Framework for Government Decision Making - Marcelo, Darwin; Mandri-Perrott, Cledan; House, Schuyler; Schwartz, Jordan (World Bank, Washington, DC, 2016)
Governments must decide how to allocate limited resources for infrastructure development, particularly since financing gaps have been projected for the coming decades. Social cost-benefit analysis provides sound project appraisal and, when systematically applied, a basis for prioritization. In some instances, however, capacity and resource limitations make extensive economic analyses across all projects unfeasible in the immediate term. This paper responds to a need for expanding the available set of tools for project selection by proposing an alternative prioritization approach that is systematic and feasible within the current resource means of government. The Infrastructure Prioritization Framework is a multi-criteria decision support tool that considers project outcomes along two dimensions, social-environmental and financial-economic. When large sets of small- to medium-sized projects are proposed, resources are limited, and basic project appraisal data (but not full social cost-benefit analysis) are available, the Infrastructure Prioritization Framework can inform project selection by combining selection criteria into social-environmental and financial-economic indexes. These indexes are used to plot projects on a Cartesian plane, and the sector budget is imposed to create a project map for comparison along each dimension. The Infrastructure Prioritization Framework is structured to accommodate multiple policy objectives, attend to social and environmental factors, provide an intuitive platform for displaying results, and take advantage of available data while promoting capacity building and data collection for more sophisticated appraisal methods and selection frameworks. Decision criteria, weighting, and sensitivity analysis should be decided and made transparent in advance of selection, and analysis should be made publicly available and open to third-party review.